Azwan did UMP proud by being named BH Varsity Icon - UMP, PNC
Azwan Affandi Md. Jahaya, 21, was announced as the Varsity Icon 2012, an event organised by Malay daily Berita Harian together with the Higher Education Ministry at Royale Chulan Hotel in Kuala Lumpur on January 25, 2013.